Epidermal Nevus Syndrome Associated with Brain Malformations and Medulloblastoma - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Researchers at Juntendo University and Tokyo Women's Medical University, Japan; and University of California, San Francisco, Ca, report a male infant with epidermal nevus syndrome associated with brainstem and cerebellar malformations and neonatal medulloblastoma.